Carrier Mobility and Lifetime in a-Si:H determined by the Moving Grating Technique - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
We have applied the moving grating technique (MGT) to amorphous silicon (a-Si:H) in order to determine the electron and hole mobilities and their lifetime. In this technique a short circuit current is induced by an interference grating moving with an adjustable velocity across the sample. The continuity equations for electrons and holes and Poisson's equation are solved to derive a theoretical expression for the short circuit current. We fit this expression to experimental data of the short circuit current as a function of the velocity and spatial period of the grating and obtain good agreement between theory and experiment. The electron mobility and the lifetime obtained from this fit is 7.7·10-2cm2/Vs and 2.1·10-6s, respectively, whereas the hole mobility is 15 times smaller than that for the electrons. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.carrie